Prevalence of typhoid fever and its associated factors among febrile patients visiting Arerti Primary Hospital, Amhara Region, north east Ethiopia - Muche, Genet; Tesfaw, Asmamaw; Bayou, Fekade Demeke (Frontiers in Public Health, 2024)
Background Typhoid fever is one of the major public health concerns in developing countries, including Ethiopia. Understanding the burden and factors contributing to the transmission and development of the disease is crucial to applying appropriate preventive and therapeutic interventions. Objective To assess the prevalence of typhoid fever and its associated factors among febrile patients visiting Arerti Primary Hospital from 1 March to 30 May 2022. Methods A facility-based cross-sectional study was employed among 326 febrile patients visiting Arerti Primary Hospital for health services. The data were collected using laboratory procedures (widal test) and a structured interviewer-administered questionnaire. The data were entered using Epi Data version 3.1 and analyzed by SPSS version 25. Logistic regression was used to determine associations between variables. P-value < 0.05 and adjusted odds ratio with 95% confidence interval were used to measure the presence and strength of associations. Results In this study, of the total 317 cases that participated, the majority (64.4%) of them were males with age ranges from 13 to 63 years. The overall prevalence of positive antigen tests for typhoid infection was 30.0% (95% CI: 25.0%−35.3%). About 66.9% of the study participants had good knowledge, 75.7% had favorable perception, and 42.3% had good infection prevention practice. Being unemployed [AOR = 7.57, 95% CI (1.98, 28.93)], being a farmer [AOR = 2.73, 95% CI (1.01, 7.41)], and having a body mass index (BMI) below 18.5 kg/m2 [AOR = 5.12, 95%CI (2.45, 10.68)] were significantly associated with typhoid fever infection. Conclusion The prevalence of typhoid fever among febrile patients was high. Typhoid fever infection was significantly associated with occupational status (being unemployed and being a farmer) and lower BMI. The level of knowledge, perception, and practice of typhoid fever infection prevention were found inadequate. Therefore, behavioral change interventions are needed at the community level.